Solve:y``-3y`+2y=e²t;y(0)=3;y-1(0)=5 by laplace transform
Let us solve "y''-3y'+2y=e^{2t},\\ y(0)=3,\\ y'(0)=5" using laplace transform:
"y\\to Y,\\ \\ y'\\to pY-3,\\ \\ y''\\to p^2Y-3p-5,\\ \\ e^{2t}\\to \\frac{1}{p-2}"
"p^2Y-3p-5-3pY+9+2Y=\\frac{1}{p-2}"
"Y(p^2-3p+2)-3p+4=\\frac{1}{p-2}"
"Y(p^2-3p+2)=\\frac{1}{p-2}+3p-4=\\frac{3p^2-10p+9}{p-2}"
"Y=\\frac{3p^2-10p+9}{(p^2-3p+2)(p-2)}=\\frac{3p^2-10p+9}{(p-1)(p-2)^2}"
"\\frac{3p^2-10p+9}{(p-1)(p-2)^2}=\\frac{A}{p-1}+\\frac{B}{p-2}+\\frac{C}{(p-2)^2}=\\frac{A(p-2)^2+B(p-1)(p-2)+C(p-1)}{(p-1)(p-2)^2}"
"3p^2-10p+9=Ap^2-4Ap+4A+Bp^2-3Bp+2B+Cp-C"
"3p^2-10p+9=(A+B)p^2+(-4A-3B+C)p+4A+2B-C"
It follows that we have the following system:
"\\begin{cases}\nA+B=3\\\\\n-4A-3B+C=-10\\\\\n4A+2B-C=9\n\\end{cases}"
"\\begin{cases}\nA=2\\\\\nB=1\\\\\nC=1\n\\end{cases}"
Therefore, "Y=\\frac{2}{p-1}+\\frac{1}{p-2}+\\frac{1}{(p-2)^2}"
Since "\\frac{1}{p-1}\\to e^t,\\ \\ \\frac{1}{p-2}\\to e^{2t},\\ \\ \\frac{1}{(p-2)^2}\\to te^{2t}," we conclude that the solution of the differential equation is the following:
"y(t)=2e^t+e^{2t}+te^{2t}."
Comments
Leave a comment